Research on neutral-point potential control of a three-level inverter - Guangjie Fu; Xinpeng Li (Institute of Advanced Engineering and Science, 2019)
Diode-clamped three-level inverters have been widely used in high voltage and high power fields because of their unique advantages. Nowadays, diode-clamped three-level inverters have become a research hotspot. In order to reduce the content of energy harmonics injected into the power grid by the inverter system, the neutral point potential needs to be controlled. This paper proposes a control method based on a proportional controller. The voltage sector was redefined and the design of the proportional controller was completed. In combination with the introduction of a new PWM technology, a smooth control of the midpoint potential was achieved. The effectiveness of the method is verified by simulation in MATLAB